Mathematical modeling of the flow of diesel-CNG fuel mixture in a pipe under the influence of a magnetic field - Abdul Wahhab, H.A. (Isfahan University of Technology, 2017)
Horizontal bubbly flow is encountered in various gas and oil facilities and industrial systems. Bubbly flow is characterized by the ability to provide large interfacial areas for heat and mass transfer. Nonetheless, horizontal bubbly flow orientation has received less attention when compared to vertical bubbly flow. This paper presents development of mathematical model and discusses the results obtained from the simulation of hydro-magnetic flow of Diesel-CNG fuel mixture in a horizontal pipe, as predicted by the developed model. The fundamental equations of unsteady, two-phase liquid-gas under an imposed magnetic field were derived and presented. Derivation procedure of the velocity distribution of the liquid and gas phases and the inverse Stokes' number of a bubbly flow are presented. These governing nonlinear partial-differential equations have been solved numerically using a Fourier-Bessel series. Results obtained from the model solution show that the axial velocities of liquid and gas, in laminar flow, have decreased and the slip ratio has increased with the increase of the magnetic field intensity. While, the magnetic field parameter, Ha increased the probability of decreasing the bubbles radii and increasing the bubbles number (n.Rb).